2023
DOI: 10.1039/d3ob01240a
|View full text |Cite
|
Sign up to set email alerts
|

Persulfate promoted carbamoylation of N-arylacrylamides and N-arylcinnamamides with 4-carbamoyl-Hantzsch esters

Qi Jing,
Fu-Ci Qiao,
Jing Sun
et al.

Abstract: Various 3,3-disubstituted oxindoles and 3,4-disubstituted dihydroquinolin-2(1H)-ones were synthesized via persulfate promoted intermolecular radical addition/cyclization of 4-carbamoyl-Hantzsch esters with N-arylacrylamides and N-arylcinnamamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…During the process, the alkyl radical intermediate was captured by TEMPO, and its corresponding adduct is detected by HR-MS analysis. Based on recent studies on S 2 O 8 2− salt-promoted cascade alkylation [44][45][46] and the above experimental results, we proposed a possible mechanism for this alkyl-centered radical-initiated cyclization transformation of alkynes (Scheme 4b). Initially, S 2 O 8 2− salt oxidized 4-cyclohexyl-DHP to generate cyclohexyl radical A and cation E, which reacted with sulfate anions to give a pyridine derivative.…”
Section: Resultsmentioning
confidence: 92%
“…During the process, the alkyl radical intermediate was captured by TEMPO, and its corresponding adduct is detected by HR-MS analysis. Based on recent studies on S 2 O 8 2− salt-promoted cascade alkylation [44][45][46] and the above experimental results, we proposed a possible mechanism for this alkyl-centered radical-initiated cyclization transformation of alkynes (Scheme 4b). Initially, S 2 O 8 2− salt oxidized 4-cyclohexyl-DHP to generate cyclohexyl radical A and cation E, which reacted with sulfate anions to give a pyridine derivative.…”
Section: Resultsmentioning
confidence: 92%
“…9 Although functionalized dihydroquinolinones have been synthesized by various methods including Friedel–Crafts cyclization, 10 transition metal-catalyzed reactions 11 and radical reactions, 12 surprisingly, the carbamoylated dihydroquinolinone synthesis has not been explored, except for a single example of the silver-catalyzed carbamoyl radical addition/cyclization of cinnamamide with 71% yield reported by Mai and co-workers 13 as part of the acyl radical cascade cyclization study (Scheme 1a) and a single example reported by Singh and co-workers 14 of photochemical carbamoylation of 2-alkynyl- N -aryl acrylamide with 76% yield using 10 mol% of Cu(OTf) 2 and a photocatalyst (Scheme 1b). Very recently, Zhou and co-workers 15 disclosed the carbamoylation of N -arylcinnamamides with 4-carbamoyl-Hantzsch ester (Scheme 1c). However, the substrate scope for this protocol is narrow and only five carbamoylated dihydroquinolinone products were synthesized with a single Hantzsch ester derivative with poor yields (28–56%) and the methodology is only suitable for installing tertiary amides.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, obvious achievements have been made, especially in the carbamoylation of N -heterocycles through a Minisci-type reaction process [ 55 , 56 , 57 , 58 ]. In recent years, radical difunctionalization reactions of alkenes employing oxamic acids or other carbamoylating reagents such as carbamoyl radical precursors have also provided a promising strategy to introduce amide groups to various complex molecules [ 59 , 60 ]. For instance, in 2021, Wang and co-workers reported persulfate-promoted difunctionalization reactions of ortho-cyanoarylacrylamides with oxamic acids to access a variety of carbamoyl quinoline-2,4-diones [ 61 ].…”
Section: Introductionmentioning
confidence: 99%